Assessment of different classification systems for predicting the risk of superior laryngeal nerve injury during thyroid surgery: a prospective cohort study - Li, Changlin; Zhang, Jiao; Dionigi, Gianlorenzo; Sun, Hui (Frontiers in Endocrinology, 2023)
Background. A multitude of anatomical variations were noted in the external branch of the superior laryngeal nerve (EBSLN). In this study, intraoperative neuromonitoring (IONM) was used to assess the potential value of the different classical EBSLN classifications for predicting the risk of EBSLN injury.. 136 patients with thyroid nodules were included in this prospective cohort study, covering 242 nerves at risk (NAR). The EBSLN was identified by observing the CTM twich and/or typical EMG biphasic waveform. The EBSLNs were classified by Cernea classification, Kierner classification, and Friedman classification, respectively. The electromyography (EMG) parameters and outcomes of vocal acoustic assessment were recorded. Results. The distribution of Cernea, Kiernea, and Friedman subtypes were, respectively, 99(41.0%), 110(45.3%), 26(10.8%), 99(41.0%), 110(45.3%), 26(10.8%), 7(2.9%) and 38(15.5%), 82(34.0%), 122(50.5%). Amplitudes changed significantly from S1 to S2, respectively, in Cernea 2A and 2B (193.7 vs. 226.6μV, P=0.019; 185.8 vs. 221.3μV, P=0.039), Kierner 2, 3 and 4 (193.7vs. 226.6μV, P=0.019; 185.8 vs. 221.3μV, P=0.039; 126.8vs. 226.0μV, P=0.015), Friedman type 2 (184.8 vs. 221.6μV,There were significant differences in F max and F range for Cernea 2A (P=0.001, P=0.001), 2B (P=0.001, P=0.038), Kierner 2 (P=0.001), Kierner 3 (P=0.001, P=0.038) and Friedman 2 (P=0.004, P=0.014). The Friedman classification showed higher diagnostic accuracy (69.8% vs. 44.3% vs. 45.0%), sensitivity (19.5% vs. 11.0% vs. 14.0%), and specificity (95.6% vs. 89.9% vs. 89.9%) than Cernea and Kierner classifications. However, the false negative rate of Friedman classification was significantly higher than other subtypes (19.5% vs. 11.0% vs. 14.0%).The Cernea 2A and 2B, Kierner 2, 3 and 4, Friedman 2 were defined as the high-risk subtypes of EBSLN. The risk prediction ability of the Friedman classification was found to be superior compared to other classifications.